The Culture of Fear and Caution in Ibn Munathir's Poetry (Journal of the College of Basic Education, 2022)
There is something that frightens and frightens the poet Ibn Munathir and causes him to panic and panic, and this is what causes him to be cautious and cautious in various situations, and it seems that the culture of panic and caution was latent in his depths, and he resorts to it and summons it in various situations for fear, or anxiety at any moment. From the moments of life, and whoever reads the poetry of the poet notices that the culture of terror is imbued in his poems, time terrifies him sometimes with its calamities and calamities, and gray hairs sometimes terrify him with the sounds of annihilation ringing in his head, and at other times he is apprehensive about separate topics dictated by life with its hustle and bustle, like the lover and her abandonment of her procrastination , or the meanness of a person, or the departure of a friend and others, and on this basis this study was made. We have decided that the limits of the study should be in the space of a poet who often carries himself into weakness and submissiveness, and is made to be timid and timid, so our choice fell on the poet Ibn Munathir, after reviewing his poems, deducing them and studying them closely